Des conflits du passé, des conflits dépassés ? Les oppositions au collectivisme dans les Tatras - Michel Lompech (Revue de Géographie Alpine)
The conflicts arising from imposed agrarian collectivism provide a key to interpreting the transformations and blockages that societies in mountain areas experienced during the second half of the 20th century. The diversity of village populations in the Slovak Tatras explains the increase in the number of such conflictual situations over the four decades of socialism. This article compares the conflicts that arose in three villages in the same mountain region with that of a fourth that was successful in its modernisation. It highlights the components and geographical effects of social change.